2014
DOI: 10.2133/dmpk.dmpk-13-rg-135
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Primary Equilibrative Nucleoside Transporter 1 mRNA Isoforms Resulting from Alternative Promoter Usage in Human Hepatocytes

Abstract: Human equilibrative nucleoside transporter 1 (hENT1) transports various nucleoside analogues into cells. Although the single hENT1 promoter region (P1) and the mRNA isoform (a1) have been characterized previously, we have recently identified additional promoter regions P2 and P3 (which primarily generate c1/2/3 mRNAs and d1/2/3/4 mRNAs, respectively) in the human liver. Therefore, this study aimed at identifying the primary hENT1 mRNA isoforms expressed in human hepatocytes, while simultaneously obtaining func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition, because we have recently demonstrated that alternative promoter usage of the ENT1 gene results in its multiple mRNA isoforms in human hepatocytes (Furihata et al . ), it was intriguing to see what ENT1 mRNA isoforms expressed in HASTR/ci35 cells. The qPCR results showed that, among the isoforms, ENT1c and ENT1d mRNA isoforms were primarily expressed in both HASTR/ci35 and prHASTR cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because we have recently demonstrated that alternative promoter usage of the ENT1 gene results in its multiple mRNA isoforms in human hepatocytes (Furihata et al . ), it was intriguing to see what ENT1 mRNA isoforms expressed in HASTR/ci35 cells. The qPCR results showed that, among the isoforms, ENT1c and ENT1d mRNA isoforms were primarily expressed in both HASTR/ci35 and prHASTR cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GIRK2, Gprotein-regulated inward-rectifier potassium channel 2; N-CAM1, neuronal cell adhesion molecule 1; NEFH, neurofilament, heavy polypeptide; NeuN, neuronal nuclei; EN1, engrailed 1; DAT, dopamine transporter; FOXA2, forkhead box protein A2; LMX1B, LIM homeobox transcription factor 1-beta. (Furihata et al 2014b), it was intriguing to see what ENT1 mRNA isoforms expressed in HASTR/ci35 cells. The qPCR results showed that, among the isoforms, ENT1c and ENT1d mRNA isoforms were primarily expressed in both HASTR/ ci35 and prHASTR cells (Fig.…”
Section: Functional Characterization Of Adenosine Transporters In Hasmentioning
confidence: 99%